Analysis on nursing culture and connotation in Shiji Yaoyu (《侍疾要语》中护理文化及内涵探析) - ZHENG Liping (郑莉萍); GUO Hailing (郭海玲); TIAN Runxi (田润溪); WANG Fang (王芳); GAO Ning (高宁); Liu Hongxin (刘红鑫) (Association of Integrative Nursing, 2023)
Shiji Yaoyu contains a wealth of nursing ideas and has laid the foundation of Traditional Chinese Medicine nursing. This article discusses the modern nursing ideology of Shiji Yaoyu from four aspects, including psychological care, life care, disease observation, drug care and nurse competency, in order to enrich the modern nursing thought and promote Chinese medicine nursing culture excavation, inheritance and development. (《侍疾要语》蕴含了丰富的护理学思想, 对中医护理学发展具有重要意义。本文从情志护理、起居护理、病情观察、用药护理、护理人员素养等方面探析《侍疾要语》 的现代护理学思想, 以充实现代护理学思想, 助力中医护理文化的挖掘、传承和发扬。)